Fish Farming Villages (Village profile)_ northwest region (Rajshahi and Rangpur) of Bangladesh - Khondker, Murshed-E-Jahan; Asgar Alam, Md. Abu Jafar; Biswas, Ashutosh; Ara, Ismat; Tabassum, Sumaya (2023)
This survey generates information about aquaculture resources, technological practices, and existing extension services and fish farming facilities through Focus Group Discussion (FGDs) and Key Informant Interviews (KIIs). It provides a scenario of the fish farming context of the northwest region of Bangladesh that aided in designing the project activities and would help in determining the long-term effects of project interventions in future.